Potable water production using two solar stills having different cover materials and fabrication costs - Riahi, A. (John Wiley and Sons Inc., 2018)
Solar stills are very cost-effective technologies used in producing potable water. This work aims to investigate the productivity of two passive double sloped solar stills fabricated with different cover materials with similar shapes; polythene film (PSS) and glass (GSS). The first solar still was made of a transparent polythene film, PVC pipes and a black painted stainless steel trough as cover, frame and basin, respectively. The second one was fabricated using glass as cover, with similar basin material. Experimental outputs indicated that GSS had 1â5 higher yield than PSS throughout the experiment. The fabrication cost of PSS was 5 times less than the cost of the GSS. The thermal energy efficiencies of PSS and GSS were obtained as 34.05 and 35.50, respectively. A mathematical model for each solar still was developed using the relationships of heat and mass transfer and their calculated and experimental productivities were in good agreement. Water quality parameters tested showed that water produced from both solar stills met the WHO standards for drinking purposes. Â© 2017 American Institute of Chemical Engineers Environ Prog, 37: 584â596, 2018. Â© 2017 American Institute of Chemical Engineers Environ Prog.